If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10x+2x=-6x-38
We move all terms to the left:
10x+2x-(-6x-38)=0
We add all the numbers together, and all the variables
12x-(-6x-38)=0
We get rid of parentheses
12x+6x+38=0
We add all the numbers together, and all the variables
18x+38=0
We move all terms containing x to the left, all other terms to the right
18x=-38
x=-38/18
x=-2+1/9
| 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | 10x+2x=-6x-38 | | x4+-3x2-10=0 | | y-11=3y-11 | | w/0.197=7.8 | | 5x10=-44-4x | | –k=–217 | | 7e+3.3=0.3 | | 3-6y=144 | | -6x^2-16x-8=0 | | –12=3(d+9) | | –12=3(d+9) | | –12=3(d+9) | | 1/3x−9=15 | | 6x+13=36 | | 6x+13=36 | | (12/x)=(-22/(x-5) | | 3*11x=4 | | F(-4)=7x+3 | | 6y^×=y+1 | | 4x3^7x=9x2^7x | | 4x3^7x=9x2^7x | | 4x3^7x=9x2^7x | | 2.77+x+3.00=3.00 | | 8(x+1)=29 | | 8(x+1)=29 |